Evaluación técnica de patrones de inyección de agua para identificar canalizaciones (2019)
Water injection process is a secondary recovery method which have been implemented in Galán oil field since 1945, as a method to maintain the reservoir pressure and provide the energy to recover remaining oil volumes and extend this asset life. It is necessary make a numerical simulation putting together all the waterflooding parameters in order to predict the reservoir behavior. This Project evaluates the water injection model (implemented in 1945) for the oil field making use of ASIA software created in 2005. it consists in analyze 7 water injection patterns of the oil field so we could identify presence of water channels in sands (A1 y A2) of Colorado Formation. Moreover, we analyzed the reservoir stratigraphy due to the point bar geometry that characterize Galan oil field. To get the variation of reservoir properties, it was calculated the reservoir heterogeneity index using the Dysktra Parson methodology; parameter of great importance for water Flow behavior. Finally, as a water production control we proposed a water conformance chemical technology, which was evaluate in ICP “Instituto Colombiano del Petróleo”: